Curcumin/Liposome Nanotechnology as Delivery Platform for Anti-inflammatory Activities via NFkB/ERK/pERK Pathway in Human Dental Pulp Treated With 2-HydroxyEthyl MethAcrylate (HEMA) - Sinjari, Bruna; Pizzicannella, Jacopo; D’Aurora, Marco; Zappacosta, Romina; Gatta, Valentina; Fontana, Antonella; Trubiani, Oriana; Diomede, Francesca (Frontiers in Physiology, 2019)
Curcumin, primary component of the spice turmeric extracted from the rhizomes of Curcuma longa, represents the major anti-oxidant and anti-inflammatory substance found in turmeric, acting thought various mechanisms not completely understood. Curcumin modulates cytokines, growth factors, transcription factors, inflammatory molecules and cell signaling pathways. During restorative dentistry practice, free resin monomers of 2-hydroxyethyl methacrylate (HEMA) propagate through dentin micro-channel and pulp into the bloodstream affecting cellular integrity. The study highlights the significance of application of curcumin bioactive component into liposomal formulations (CurLIP) to restore the homeostasis of dental pulp stem cells (hDPSCs) in response to 3 and 5 mmol L-1 HEMA treatment. Cell proliferation in combination with changes of the morphological features, proinflammatory cytokines secretion as Interleukin (IL) 6, IL8, Monocyte Chemoattractant Protein-1 (MCP1) and Interferon-gamma (IFNɣ) were assayed along with the nuclear factor (NF)-kB, an inducible transcription factor involved in the activation of several cell processes associated to extracellular signal-regulated kinases (ERK) and posphorylated (p-) ERK pathway. Our results showed a decreased cell proliferation, morphological changes and upregulation of IL6, IL8, MCP1 and IFNɣ in presence of 3 and 5 mmol L-1 HEMA treatment. CurLIP therapy in hDPSCs provokes an increase in cell proliferation and the block of inflammatory cytokines secretion through the inhibitory regulation of NFkB/ERK and pERK signaling cascade. The natural nanocarrier CurLIP influences numerous biochemical and molecular cascades causing anti-inflammatory properties in response to HEMA treatment in human dental pulp stem cells, representing an innovative endodontic formulation able to improve the quality of dental care with a major human community impact.